Gender Differences in Economics Course-Taking and Majoring : Findings from an RCT - Halim, Daniel; Powers, Elizabeth T.; Thornton, Rebecca (World Bank, Washington, DC, 2021)
This paper reports on gender differences in responses to a randomized controlled trial that provided encouragement and information nudges to take subsequent economics courses and major in the subject for students enrolled in large introductory economics classes at a large elite public university. Two treatments combined encouragement to major in economics with information on either financial or prosocial returns to the major. Men receiving either treatment were more likely to take an additional economics course, but not to major in economics. In contrast, the treatments were not estimated to significantly affect women’s course-taking and majoring. Two treatment mediators are also examined: expected versus actual grade and having a female teaching assistant. There were also differing effects of mediators on treatment responses for men and women. Women were more nudge-able to take another course when they received a better-than-expected introductory class grade, and men were more nudge-able to take another course when they had a female teaching assistant.